2008
DOI: 10.1200/jco.2007.11.0726
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anastrozole on Bone Mineral Density: 5-Year Results From the Anastrozole, Tamoxifen, Alone or in Combination Trial 18233230

Abstract: Anastrozole is associated with accelerated bone loss over the 5-year treatment period. However, although patients with pre-existing osteopenia are likely to require monitoring and bone-protection strategies, patients with normal BMD would not appear to require monitoring beyond the recommendation for healthy postmenopausal women. The effect of anastrozole on bone should be weighed against its superior efficacy and better tolerability profile versus tamoxifen in the main ATAC trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
221
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 369 publications
(240 citation statements)
references
References 29 publications
10
221
2
7
Order By: Relevance
“…In postmenopausal women with recently diagnosed early breast cancer, the use of an aromatase inhibitor in the adjuvant setting has been associated with an average bone loss of around 2% per year in the LS and 1.5% at the hip [9][10][11][12]. In IES, we have previously reported that significant changes in BTM and BMD appeared within 6m of switching from tamoxifen to exemestane [9].…”
Section: Discussionmentioning
confidence: 99%
“…In postmenopausal women with recently diagnosed early breast cancer, the use of an aromatase inhibitor in the adjuvant setting has been associated with an average bone loss of around 2% per year in the LS and 1.5% at the hip [9][10][11][12]. In IES, we have previously reported that significant changes in BTM and BMD appeared within 6m of switching from tamoxifen to exemestane [9].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because BMD measurement occurred within a short time from BC diagnosis (B15 days) in this study, bone loss that would occur during BC treatment is not considered. For example, AIBL and ovarian suppression-associated bone loss are most severe within the first 3 years of beginning therapy, but remain elevated for the duration of therapy (Howell et al, 2005;Thurlimann et al, 2005;Coombes et al, 2007;Eastell et al, 2008;Gnant et al, 2008). Therefore, patients are likely to experience additional decreases in BMD during BC treatment, making the management of bone health an increasing concern.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to natural bone loss associated with ageing, therapies for BC can impair bone health directly, or indirectly by disrupting estrogen production and signalling (Pfeilschifter and Diel, 2000). For example, ovarian suppression using agents such as goserelin in premenopausal women, or aromatase inhibitor (AI) therapy in postmenopausal women, can result in substantial bone loss (Eastell et al, 2008;Gnant et al, 2008). Adjuvant AI therapy is now the standard of care for postmenopausal women with HR þ BC because of its superior disease-free survival results and more favourable side-effect profile (particularly with regard to venous thrombosis and endometrial cancers) compared with tamoxifen (Howell et al, 2005;Thurlimann et al, 2005;Coombes et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study among women with breast cancer, anastrozole was associated with decreased bone mineral density after 5 years of treatment [41]. Letrozole may be preferred because it does not cause hypoestrogenemia and its related adverse effects, perhaps because the small dose of letrozole used in our study (2.5 mg) is insufficient to inhibit the production of estradiol in the ovaries [40••].…”
Section: Aromatase Inhibitorsmentioning
confidence: 99%